Socio-Political Conflict Dynamics After the 2024 Polewali Mandar Election: Dinamika Konflik Sosial-Politik Pasca Pemilihan Umum Polewali Mandar 2024 - Ahmad Ilham; Jumadi Jumadi; Hasruddin Nur (Universitas Muhammadiyah Sidoarjo, 2026)
General Background Regional head elections represent a core mechanism of local democracy in Indonesia, intended to facilitate political participation and power circulation at the subnational level. Specific Background In practice, post-election phases frequently generate socio-political tensions, particularly in communities with strong kinship structures and identity-based affiliations, as observed in Polewali Mandar following the 2024 regent election. Knowledge Gap Existing studies often approach post-election conflict through legalistic or security-centered perspectives, leaving limited understanding of conflict as a prolonged social process embedded in everyday relations and digital interactions. Aims This study aims to analyze the dynamics of post-election socio-political conflict in Polewali Mandar, identify structural, cultural, and communicative factors driving the conflict, and examine its social consequences. Results Using a qualitative descriptive approach through interviews, observation, and documentation, the findings reveal polarized supporter groups, non-physical and symbolic conflicts, the circulation of hoaxes and hate speech in digital spaces, weakened family and community interactions, and declining trust in democratic institutions. Contributing factors include identity politicization, money politics, questioned neutrality of village officials and civil servants, elite rivalries, and low political literacy. Novelty This study conceptualizes post-Pilkada conflict not merely as an electoral event but as a socially embedded process shaped by kinship, local identity, patronage networks, and digital communication. Implications The findings underscore the need for participatory and local-wisdom-based conflict resolution strategies to support democratic consolidation and restore social cohesion at the local level. Highlights: Post-election tensions manifested predominantly through symbolic, non-violent, and latent social frictions. Identity-based alignments and elite rivalries intensified polarization within families and local communities. Digital communication spaces played a central role in sustaining distrust and prolonged social tension. Keywords: Socio-Political Conflict, Pilkada, Local Democracy, Polewali Mandar, Conflict Resolution.